Methods used in Quantifying Green House Gas Emissions from the Food Systems - Ngaiwi, Mary Eyeniyeh; Vanegas Cubillos, Martha Cristina; Sylvester, Janelle Marie; Verchot, Louis Vincent; Castro Nunez, Augusto Carlos (2024)
This document encompasses the a collection of studies from literature that have used different methods to estimate greenhouse gas emissions from the different stages of the food system.